2010
DOI: 10.1002/ijc.25397
|View full text |Cite
|
Sign up to set email alerts
|

PD‐1 and PD‐L1 upregulation promotes CD8+ T‐cell apoptosis and postoperative recurrence in hepatocellular carcinoma patients

Abstract: Programmed death 1 (PD-1) and its ligand (PD-L1) play pivotal roles in regulating host immune responses. However, the inhibitory effects of this pathway on the function of cytotoxic CD8 1 T lymphocytes, the main effector cells in hepatocellular and blocking PD-L1 reversed this effect. Therefore, this study extends our knowledge of the role of the PD-1/PD-L1 pathway in tumor evasion and provides evidence for a new therapeutic target in HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
326
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(343 citation statements)
references
References 38 publications
9
326
2
6
Order By: Relevance
“…Similarly, Sawada et al showed that PD-1 is highly expressed on the CTLs of patients vaccinated with GPC3 [34]. PD-1/PD-L1 expression in tumor was significantly correlated with HCC stage, local recurrence rate and poor prognosis [35]. PD-1/PD-L1 expression in circulating cells was reported to correlate with the poor prognosis in HBV-positive HCC patients who underwent cryoablation [36].…”
Section: Pd-1mentioning
confidence: 90%
“…Similarly, Sawada et al showed that PD-1 is highly expressed on the CTLs of patients vaccinated with GPC3 [34]. PD-1/PD-L1 expression in tumor was significantly correlated with HCC stage, local recurrence rate and poor prognosis [35]. PD-1/PD-L1 expression in circulating cells was reported to correlate with the poor prognosis in HBV-positive HCC patients who underwent cryoablation [36].…”
Section: Pd-1mentioning
confidence: 90%
“…In addition, these neutrophils may also secrete agents that promote tumor cellular proliferation, angiogenesis, invasion and metastasis (46), and they may inhibit T cells (47). As important components of the non-specific and adaptive immune response, lymphocytes are able to destroy tumor cells via cytotoxic cells and cytokine secretion (48). A decreased lymphocyte count results in reduced tumor resistance (49).…”
Section: Discussionmentioning
confidence: 99%
“…13,18 This technique may have a renew interests in light of the expression of programmed cell death 1 (PD1) pathway in HCC and recent encouraging outcome demonstrated in patients treated with Nivolumab. 19,20 An international registry of clinical trials on CIK was established in 2010 by SchmidtWolf et al, with an aim to collect clinical data and standardize treatment of patients with cancer using CIK cells. 21 In previously published studies, CIK treatment has been shown to significantly improve patient survival, especially when combined with minimally invasive treatments to give a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%